Analysis of Factors Associated with Wus's Decision to Use an IUD in the Working Area of the Maja Public Health Center, Lebak Regency in 2024 - Indah Mulia Herwisdiane; Wayan Aryawati; Fitri Ekasari; Dessy Hermawan; Dhiny Easter Yanti (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Birth control has become a global issue that is very important in maintaining a balance between population growth and available resources. One contraceptive method that is often used is the IUD. The prevalence of IUD/AKDR family planning acceptors in Indonesia is 3.8% and in Banten it is 6.09%. IUDs have been a major focus of long-acting contraceptive research due to their high effectiveness, reversibility, and potential additional health benefits. The aim of the research is to determine the factors related to WUS's decision to use an IUD. This type of quantitative research with a cross sectional design. The population in the study, namely women of childbearing age in the Maja Health Center Working Area, amounted to 9,394 people and a sample of 369 people using the cluster random sampling technique . Data analysis used univariate, bivariate ( chi square), and multivariate ( multiple logistic regression). The results of bivariate analysis showed that there was no relationship between age (p=0.405), parity (p=0.837), and occupation (p= 0.875) with WUS's decision to use an IUD. Meanwhile, education (p=0.004), knowledge (p=0.000), attitude (p=0.038), husband's support (p=0.035), and support from health workers (p=0.029) influenced WUS' decision to use an IUD. The factor most related to WUS's decision to use an IUD was knowledge with OR= 9.591. The conclusion of this research is that the dominant factor related to the decision to use an IUD is knowledge. WUS should actively seek information through trusted sources such as consulting with medical personnel at community health centers or reading accurate health literature.